2013
DOI: 10.1155/2013/590416
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Vaginal Discharge among Pregnant Women: Pattern of Occurrence and Association in a Population-Based Survey

Abstract: This study aimed to assess the prevalence of pathological vaginal discharge and to describe risk factors associated with pregnant women. All women living in the city of Rio Grande, Southern Brazil, who gave birth in 2010 were included in the study. A standardized questionnaire was administered to collect information on demographic, reproductive, and health-related factors and morbidity during pregnancy. The chi-square test was used to compare proportions, and multivariate Poisson regression with robust varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
1
16
2
2
Order By: Relevance
“…This is in contrast to a study done by Fonseca TM et al, in Brazil which showed that history of pathological vaginal discharge during pregnancy was significantly associated with threatened premature labour. 9 We did not observe a significant correlation between a positive family history of preterm birth and preterm delivery (p=0.821). This is in contrast to a study published by Sherf Y et al, which concluded that family history of preterm delivery is an independent risk factor for recurrence of preterm birth in the subsequent generation.…”
Section: Resultsmentioning
confidence: 52%
“…This is in contrast to a study done by Fonseca TM et al, in Brazil which showed that history of pathological vaginal discharge during pregnancy was significantly associated with threatened premature labour. 9 We did not observe a significant correlation between a positive family history of preterm birth and preterm delivery (p=0.821). This is in contrast to a study published by Sherf Y et al, which concluded that family history of preterm delivery is an independent risk factor for recurrence of preterm birth in the subsequent generation.…”
Section: Resultsmentioning
confidence: 52%
“…Our long experience in the management of miscarriage have been shown that the majority of the histopathology studies of the products of conception often reveal infected products which suggests that the infection is one of the primary causes of miscarriage. During pregnancy genital mucosa becomes thinner and has greater surface area, making pregnant women more susceptible to infection [13]. Furthermore, it is reported that infection such as chlamydia trachomatis is an important causative factor of miscarriage and the association between chlamydia positive diagnostic test and miscarriage is significant (OR 2.41,95% CI 1.32-3.35, P<0.01) [8].…”
Section: Discussionmentioning
confidence: 99%
“…La gestación conduce a un desequilibrio del microambiente vaginal, favoreciendo la proliferación de microorganismos e incrementando la gravedad y recurrencia de infecciones. Diversos estudios han mostrado que las mujeres más jóvenes poseen mayor tendencia a tener flujo vaginal patológico durante la gestación [12][13][14] . Así pues, la población considerada en este estudio presentó una mediana de edad de 23 años, cifra similar a la obtenida por algunos estudios.…”
Section: Discussionunclassified